(untitled) (Revista horizonte, 2022)
The purpose of this study was to determine the effect of physical-mental practice (PFM) and physical practice (PM) on the soccer penalty kick accuracy. A total of 11 college students who belong to the menâ€™s soccer team were randomly assigned to one of the two groups. Accuracy was assessed by marking the soccer goal with four target zones at the corners (10 pints to score in each zone). The intervention consisted of 2 sessions. In the first session, the pretest, the experimental practice (PFM o PM), and the acquisition test for accuracy. One week later, the retention test was assessed (second session). A fatigue test was assessed for the acquisition and retention test. A PearsonÂ´s correlation indicated that fatigue is not related to precision in neither group. A two-way ANOVA with repeated measures in the last factor [group (2) x measurement (3)] found a non-significant effect in precision test for neither interaction, group, nor measurement. These results suggest that the type of practice had no effect on the precision in a soccer penalty kick.